KAJIAN EFEKTIFITAS SISTEM INFORMASI PENJUALAN ONLINE: STUDI KASUS WWW.TOKPRADA.COM - Hari Sugiarto (Paradigma, 2013)
Costumers’ satisfaction and loyalty are the most important things in business competition. Threevariables that will be used in this research are Quality System, Information Quality, and ServiceQuality. These factors may impact the users’ satisfaction. The research proposes a combinationframework model of DeLone and McLean models (2003) and Akbar and Parvez models (2009)and Structural Equation Model (SEM) was used to analyze the questionnaire data. The result ofthe analysis shows that the model does not fit with the population. In other hand, the model onlyrepresents the samples. Based on proposed model, Quality System and Information Quality doesnot significantly affect users’ satisfaction whereas the Quality service does and users’ satisfactioninfluences users’ loyalty.Keywords: E-commerce, SEM and AMOS